IceCube Search for Dark Matter Annihilation in nearby Galaxies and Galaxy Clusters - Aartsen, MG; Abbasi, R; Abdou, Y; Ackermann, M; Adams, J; Aguilar, J; Ahlers, M; Altmann, D; Auffenberg, J; Bai, X; Baker, M; Barwick, S; et al. (2013)
We present the results of a first search for self-annihilating dark matter in nearby galaxies and galaxy clusters using a sample of high-energy neutrinos acquired in 339.8 days of live time during 2009/10 with the IceCube neutrino observatory in its 59-string configuration. The targets of interest include the Virgo and Coma galaxy clusters, the Andromeda galaxy, and several dwarf galaxies. We obtain upper limits on the cross section as a function of the weakly interacting massive particle mass between 300 GeV and 100 TeV for the annihilation into b bbar, W+W-, τ+τ-, μ+μ-, and ν ν bar. A limit derived for the Virgo cluster, when assuming a large effect from subhalos, challenges the weak interacting massive particle interpretation of a recently observed GeV positron excess in cosmic rays.